Studi Literatur Tentang Kesehatan Mental Dalam Perspektif Islam dan Psikologi: Faktor dan Strategi Penanganannya - Fayyaza Ariefa Yusvinanda; Indah Sari; Aceng Kosasih (Yayasan Al-Afif, 2025)
This literature study addresses the issue of mental health in the context of Islam and psychology, focusing on influencing factors and intervention strategies. The research aims to compare conceptual frameworks and identify effective approaches for mental health management. Data were collected through a systematic review of recent journal articles, books, and credible online sources. Findings reveal that Islam emphasizes the balance of physical, intellectual, and spiritual aspects through worship, remembrance, and social relations, while psychology highlights individual well-being, stress management, and social functioning. Key factors include faith, religious practices, and social support in Islam, and biological, psychological, and social aspects in psychology. The integration of both perspectives offers a holistic and contextual model for mental health intervention, especially in religious communities. This study suggests that interdisciplinary collaboration is crucial for developing inclusive, effective mental health education and services.